PARADIGM SHIFT IN INFORMATION PRODUCTION AND DISTRIBUTION IN THE DIGITAL ERA - Denny Setiawan Batubara; Tuty Mutiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The rapid development of information and communication technology in the last decade has fundamentally transformed the paradigm of information production and distribution. The traditional “one-to-many” communication model that characterized conventional media has shifted toward a “many-to-many” configuration, enabling broader public participation in content creation and dissemination. This phenomenon signifies the emergence of an open, interactive, and decentralized digital communication ecosystem. The transformation is driven by media convergence, the rise of social media platforms, and the emergence of new actors such as content creators, citizen journalists, and influencersthat blur the boundaries between information producers and consumers. This study aims to analyze how the paradigm of information production and distribution has shifted in the digital era by examining the roles of actors, production processes, and algorithmic distribution mechanisms. A qualitative research approach is employed to explore the dynamics of digital media in Indonesia by integrating theories of media convergence, media ecology, and digital communication ethics. The findings indicate that algorithms have become new gatekeepers in digital platforms, determining visibility and reach while creating a paradox between popularity and information quality. Moreover, the study reveals a significant change in audience behavior, with a growing preference for audiovisual formats that compel news organizations to adopt multiplatform production strategies. However, this shift also triggers a crisis of authority and ethics in information distribution due to the proliferation of unverified content. Therefore, effective media convergence management and digital literacy are essential to maintain credibility and uphold social responsibility in the digital ecosystem. Ultimately, the research concludes that the paradigm shift in digital communication is not merely technological but epistemological, requiring a redefinition of journalistic professionalism, ethical values, and public information governance.